2011
DOI: 10.1007/s12600-011-0184-2
|View full text |Cite
|
Sign up to set email alerts
|

Activity of ß-1,3-glucanase and ß-1,4-glucanase in two potato cultivars following challenge by the fungal pathogen Alternaria solani

Abstract: Early blight of potato, caused by Alternaria solani, is a ubiquitous disease in many countries around the world. Our previous screening of several Iranian potato cultivars found that variation in resistance exists between two cultivars: 'Diamond' and 'Granula'. Cultivar Diamond is more resistant to multiple isolates of A. solani when compared to cv. Granula. Furthermore, we have found that different pathogen isolates have varying degrees of infection. We monitored the activities of two pathogen-related (PR) gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Pathogenesis-related (PR) proteins are important in plant defense against pathogens, some PR proteins have been identified as chitinases and β-1,3-glucanases [21] . The high activities of these two proteins was potentially related to resistance to Alternaria solani in potato [22] . The synthesis of PR proteins is regulated at the transcriptional level and it has often been suggested that the collection of PR proteins may be effective in inhibiting pathogen growth and inducing systemic acquired resistance [23,24] .…”
Section: Introductionmentioning
confidence: 99%
“…Pathogenesis-related (PR) proteins are important in plant defense against pathogens, some PR proteins have been identified as chitinases and β-1,3-glucanases [21] . The high activities of these two proteins was potentially related to resistance to Alternaria solani in potato [22] . The synthesis of PR proteins is regulated at the transcriptional level and it has often been suggested that the collection of PR proteins may be effective in inhibiting pathogen growth and inducing systemic acquired resistance [23,24] .…”
Section: Introductionmentioning
confidence: 99%